2018
DOI: 10.1016/j.jare.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based estimation of an automotive magnetorheological brake system performance

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Dalam bidang rekayasa dan engineering, umumnya digunakan piranti lunak untuk membantu penyelesaian kasus yang telah ditentukan (Kalikate, Patil, & Sawant, 2018). Salah satu software yang biasa digunakan dalam perancangan adalah ANSYS (Chandra, 2009).…”
Section: Pendahuluanunclassified
“…Dalam bidang rekayasa dan engineering, umumnya digunakan piranti lunak untuk membantu penyelesaian kasus yang telah ditentukan (Kalikate, Patil, & Sawant, 2018). Salah satu software yang biasa digunakan dalam perancangan adalah ANSYS (Chandra, 2009).…”
Section: Pendahuluanunclassified
“…Six pairs of coils were evenly distributed on both sides of the MRB to generate high-intensity magnetic field. The test results showed that the braking torque of the designed MRB was large, the input current can accurately control the braking torque, and the response time was less than 100 ms. Kalikate et al (2018) conducted simulink modeling and simulation on MRB for two-wheeler vehicles, and concluded that in order to meet the requirements of Indian braking standard of IS 14664:1999, six or more disks were required for MRB. However, the size and weight constraints may not allow the use of such brakes for two-wheeler vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the magnetic dampers as common equipment for utilizing magnetic fluids, there are other applications to use them. The other applications of MR fluid in various industries consist of building industry (He et al, 2017;Heo et al, 2017;Xu et al, 2017;Yanik and Aldemir, 2019;Zafarani and Halabian, 2018), polishing machine (Barman and Das, 2018;Grover and Singh, 2018;Kansal et al, 2018;Khatri et al, 2017;Mosavat and Rahimi, 2019;Zhang et al, 2018), MR elastomers (Agirre-Olabide and Elejabarrieta, 2018;Bastola and Lia, 2018;Bica et al, 2019;Vemuluri et al, 2018;Yao et al, 2018), and brake manufacturing (Attia et al, 2017;Dai et al, 2019;Kalikate et al, 2018;Kumbhar et al, 2015;Topcu et al, 2018). By the development of micro-machines, a new application of this semi-active equipment emerged (Liu et al, 2016), such as the bonding pressure of the microelectronics packaging instrument that requires a constant loading force of 5 N (Li et al, 2016) and in a flip chip solder which is necessary to load an electronic chip with a damping force of less than 10 N via a power control system with a maximum error of 1%; so, it is necessary to design and optimize MR damper which obtains damping force less than 10 N for slower landing (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%